Effectiveness of “GUCHIRO” as an Alternative Food to Prevent Anemia in Pregnant Women - Hindratni, Findy; Sari, Septi Indah Permata; Fathunikmah, Fathunikmah (Poltekkes Kemenkes Riau, 2024)
Anemia in pregnant women can have serious impacts, including stunted fetal growth and the risk of bleeding. This study developed an innovative product “GUCHIRO”, a sago mocha with rosella flower jam (Hibiscus sabdariffa L.), to prevent non-pharmacological anemia. This study aims to evaluate the effectiveness of GUCHIRO in increasing the hemoglobin level of pregnant women. The method used was quantitative analytic with a sample of 25 pregnant women, carried out from January to October 2024 at the Riau Health Ministry Poltekkes Laboratory and PMB Dince Safrina Pekanbaru. The results showed that the average hemoglobin level increased from 10.281 mg/dL before consumption of GUCHIRO to 11.014 mg/dL after consumption. The difference in hemoglobin levels was significant with a value of p=0.000. This study shows that GUCHIRO is effective in increasing the hemoglobin level of pregnant women and can be a non-pharmacological alternative for the prevention of anemia. Keywords: GUCHIRO, anemia, pregnant women